2019
DOI: 10.1177/0361198119827928
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intersection Lighting Design on Drivers’ Perceived Visibility and Glare

Abstract: A systems-level approach to intersection lighting design has shown that illuminating the intersection box increases drivers’ nighttime visual performance. However, for an intersection lighting design to be effective and accepted, it should not only maximize visual performance but also enhance perceived visibility and minimize glare. The goals of this study were to assess the effects of different intersection lighting designs on these two outcomes. Visibility was assessed with respect to a pedestrian, several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Visual performance typically plateaued (no increase in visual performance with a corresponding increase in illuminance) between 8 and 12 lux 11/01/2018 illuminance levels. While there was no difference between the three lighting configurations in terms of pedestrian visibility, the Box lighting configuration resulted in higher perceived target and intersection visibility and lower perceived glare [16]. Perceived visibility ratings also plateaued between 8 and 12 lux illuminance levels in this lighting configuration.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Visual performance typically plateaued (no increase in visual performance with a corresponding increase in illuminance) between 8 and 12 lux 11/01/2018 illuminance levels. While there was no difference between the three lighting configurations in terms of pedestrian visibility, the Box lighting configuration resulted in higher perceived target and intersection visibility and lower perceived glare [16]. Perceived visibility ratings also plateaued between 8 and 12 lux illuminance levels in this lighting configuration.…”
Section: Introductionmentioning
confidence: 73%
“…There were five target locations as described in [15] (Figure 1). The simulated pedestrian was same as the pedestrian described in the perceived visibility experiment [16] (Figure 2) and was located at the Near Right location (see Figure 1). Pedestrian location for photometric measurements was moved slightly to the left of the actual location used in the subjective ratings experiment, in interest of saving time and to facilitate capturing of all object locations with a single image.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been also observed that increased intensity of road lighting decreases the number of accidents with pedestrian of 59%. Similarly, increased intensity of roadway lightning and installation of flashing warning signs acts with a reduction of pedestrian crashes of 57% in nighttime and a significant decrease in daytime, about 21%(Zgeer et al, (2006);Nassar et al, (2011);Scott et al, (2012);Bassani et al, (2012);Niaki et al, (2014);Bichicchi et al, (2017);Gibbons at al., (2015);Wei et al, (2016); Bullough et al, (2017 Bullough et al, ( ), (2021;Wang et al, (2018);Gbologah et al, (2019);Bhagavathula et al, (2019Bhagavathula et al, ( ), (2020;Costa et al, (2017), (…”
mentioning
confidence: 99%